Analysis of Sharia Economic Law on the Digital Consumptive Credit Model: the Potential of Usury in Buy Now Pay Later - Antika Yuni Arsita; Shofiah Nur Hikmah; Dwi Liza Salsabila; Katon Adin Novaga; Baidhowi (Takaza Innovatix Labs Ltd., 2025)
Advances in digital technology are currently driving the birth of a buy-now pay later-based digital financing model that is increasingly popular in people's consumptive transactions. This scheme offers easy access to financing without a credit card but through a payment deferral mechanism with an additional fee. However, from the perspective of sharia economic law, this practice raises juridical problems related to the potential for usury, especially in the aspect of adding value required for the suspension of payment. This research was conducted using a normative juridical method with a legislative and conceptual approach. The purpose of this study is to analyze and find out whether the financing mechanism in the buy now pay later scheme substantively represents the practice of riba that is prohibited in sharia economic law. In addition, this study also aims to examine how the perspective of Islamic economic law on the transformation of digital consumptive credit based on buy now pay later in the context of financial technology developments. The results of the study show that the buy now pay later scheme does provide easy access to credit for consumers. However, in practice, there is still a potential for elements of riba and gharar that are not in accordance with the principles of sharia economic law. Some buy now pay later platforms have been proven to impose interest and late fines that are substantially contrary to the principle of the qardh contract. Therefore, based on the perspective of sharia economic law, the buy now pay later mechanism needs to be reviewed and adjusted to better reflect the principles of transparency, fairness and balance of the parties so that it can meet sharia compliance standards..